2011
DOI: 10.1016/j.ijgo.2010.09.010
|View full text |Cite
|
Sign up to set email alerts
|

Enoxaparin versus unfractionated heparin in the management of recurrent abortion secondary to antiphospholipid syndrome

Abstract: LMWH plus LDA was successfully used as an alternative to UFH plus LDA in the management of recurrent abortion secondary to APS. The results highlight the need for a larger randomized controlled trial to determine whether LMWH plus LDA should be the treatment of choice for recurrent abortion secondary to APS. Clinicaltrials.gov NCT01051778.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
60
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(64 citation statements)
references
References 22 publications
4
60
0
Order By: Relevance
“…[107] A small trial showed comparable results with LMWH plus aspirin as an alternative to unfractionated heparin and aspirin in the management of recurrent miscarriage secondary to APS. [108] The consensus is combination of low molecular weight heparin and aspirin is superior to aspirin alone in achieving more live births. Therefore, it is recommended treatment for recurrent miscarriages with antiphospholipid syndrome[109110] (Evidence level I).…”
Section: Methodsmentioning
confidence: 99%
“…[107] A small trial showed comparable results with LMWH plus aspirin as an alternative to unfractionated heparin and aspirin in the management of recurrent miscarriage secondary to APS. [108] The consensus is combination of low molecular weight heparin and aspirin is superior to aspirin alone in achieving more live births. Therefore, it is recommended treatment for recurrent miscarriages with antiphospholipid syndrome[109110] (Evidence level I).…”
Section: Methodsmentioning
confidence: 99%
“…related at least in part to placental thrombosis. [72][73][74][75][76][77][78][79] Given the preferable profile of LMWH to UFH from a safety and side-effect standpoint, many practitioners choose to administer prophylactic-dose LMWH.…”
Section: Antiphospholipid Antibody Syndromementioning
confidence: 99%
“…Low-molecular-weight heparin has demonstrated similar efficacy to unfractionated heparin in prospective studies on obstetric APS. 62,63 In patients refractory to these treatment strategies, an additional use of steroids, intravenous immunoglobulin, and plasmapheresis has shown benefit in case reports.…”
mentioning
confidence: 99%